In search for sustainable alternatives to lawns - Hellner, Ameli; Vilkénas, Julia (2014)
A large part of Sweden’s green, urban landscape is covered by lawns. Approximately 80 000 ha of maintained grass lawns are part of public courtyards, schoolyards, parks, golf courses, sport fields and traffic environments. Beyond this figure, the lawn is also an essential element in most private villa-gardens. Lawns have become a universal phenomenon through the dispersion of landscape aesthetics from the Western world. Even though there are many wild living grass species in Scandinavia only a few of these are used in today’s lawns. Lawns in Sweden mostly consist of Festuca rubra, Poa pratensis, Agrostis capillaris, Phleum pratense, Agrostis stolonifera and Lolium perenne. The lawn is a cultural product that is designed to always look the same; lush, green and well maintained. To achieve this aesthetic expression the lawn requires a constant maintaining by mowing and fertilization, which lead to pollution of air and soil. Since the lawn only consists of a few grass species, the dispersion of lawns also leads to a homogenization of plant material and is a threat to urban biodiversity. Today lawns are seen as a natural part of the urban landscape without questioning their functional, ecological or aesthetic value. To implement other options with high biodiversity in urban environments is a challenge since the homogenized lawn has become a natural part of the urban fabric. This phenomenon derives from globalization, media, social pressure and the idea that nature is wild and must be controlled. The lawn has historically become such a common feature of the urban environment that it is difficult for people to imagine other alternatives. The goal with this essay has been to make a proposal of a demonstration garden at campus Ultuna, showing examples of sustainable alternatives to the lawn. Hopefully the demonstration garden will be used as inspiration for a change of the classic lawn in urban environments. Our final design proposal consists of eight examples of ecological, social and economically sustainable alternatives to lawn. The alternative lawns are suited to the habitat on the site, has a dynamic aesthetic expression and consists of native flora. The demonstration garden has been designed as a conceptual project that will hopefully be implemented in the near future.